Pelagic Methane Sink Enhanced by Benthic Methanotrophs Ejected From a Gas Seep. Issue 20 (21st October 2021) - Jordan, S. F. A.; Gräwe, U.; Treude, T.; van der Lee, E. M.; Schneider von Deimling, J.; Rehder, G.; Schmale, O.
Abstract: Cold seeps represent hot spots of seabed‐derived methane emissions to the water column, where physical and biological barriers regulate transport of methane to the atmosphere. In our study, we used a methane point source in the North Sea to investigate water‐column methane dynamics within the dispersing plumes. The study is based on methane concentration, distribution and activity of methane‐oxidizing bacteria (MOB), and oceanographic observations. Our findings suggest the ejection of benthic MOB into the water column by sediment resuspension and gas‐bubble‐mediated transport. An applied particle‐tracking model demonstrated that the ejection of 4.29 ± 1.9 × 10 12 MOB cells s −1 from the seep site would produce the MOB abundance detected in the down‐current water body. The benthic MOB inoculant accelerated methane oxidation rates by a factor of five. Our study highlights the importance of the bentho‐pelagic transport of microorganisms at seep sites and their feedback on the pelagic methane sink. Plain Language Summary: In the marine system, the greenhouse gas methane is primarily produced in sediments. Under specific geologic conditions, methane can accumulate in the sediment and be released as gas bubbles. Such gas seepage also occurs at abandoned oil or gas‐drilling sites. However, direct transport of methane from submarine seeps to the atmosphere is only likely in shallow regions, as ascending bubbles release most of their methane quickly into the surrounding water. Methanotrophic bacteria living in the top sediment layer and the water column metabolize the dissolved methane. These methanotrophs can be transported from the sediment into the water column by gas bubbles or sediment resuspension. To understand the effect of the transported methanotrophs on the methane removal in the water column, we focused on an abandoned oil‐drilling site in the North Sea that has been emitting methane gas bubbles since 1990. We took water samples from different depths near the drilling site and this showed that the transported methanotrophs accelerated methane oxidation rates by a factor of about five. Additionally, we used a numerical model to estimate the number of methanotrophs ejected from the seep site and traced their distribution in the dispersing plume. Key Points: The ejection of benthic methanotrophs from the gas seep site can explain the methanotroph's abundance in the down‐current methane plume The seep‐induced inoculation of the water column with methanotrophs decreased the pelagic methane turnover time by a factor of about five Our particle‐tracking model showed that tides controlled the areal distribution of methane and methanotrophs released by the seep site